Polyvinyl-Pyrrolidone-Coated Silver Nanoparticles—The Colloidal, Chemical, and Biological Consequences of Steric Stabilization under Biorelevant Conditions - Rónavári, Andrea; Bélteky, Péter; Boka, Eszter; Zakupszky, Dalma; Igaz, Nóra; Szerencsés, Bettina; Pfeiffer, Ilona; Kónya, Zoltán; Kiricsi, Mónika (International journal of molecular sciences, 2021)
(1) Background: Several properties of silver nanoparticles (AgNPs), such as cytotoxic, anticancer, and antimicrobial activities, have been subjects of intense research; however, important aspects such as nanoparticle aggregation are generally neglected, although a decline in colloidal stability leads to a loss of the desired biological activities. Colloidal stability is affected by pH, ionic strength, or a plethora of biomolecules that interact with AgNPs under biorelevant conditions. (2) Methods: As only a few studies have focused on the relationship between aggregation behavior and the biological properties of AgNPs, here, we have systematically evaluated this issue by completing a thorough analysis of sterically (via polyvinyl-pyrrolidone (PVP)) stabilized AgNPs that were subjected to different circumstances. We assessed ultraviolet–visible light absorption, dynamic light scattering, zeta potential measurements, in vitro cell viability, and microdilution assays to screen both colloidal stability as well as bioactivity. (3) Results: The results revealed that although PVP provided outstanding biorelevant colloidal stability, the chemical stability of AgNPs could not be maintained completely with this capping material. (4) Conclusion: These unexpected findings led to the realization that stabilizing materials have more profound importance in association with biorelevant applications of nanomaterials than just being simple colloidal stabilizers.